Transport of Glucose, Gluconate, and Methyl α-D-Glucoside by Pseudomonas aeruginosa - Guymon, L. F. (1974)
Glucose transport by Pseudomonas aeruginosa was studied. These studies were enhanced by the use of a mutant, strain PAO 57, which was unable to grow on glucose but which formed the inducible glucose transport system when grown in media containing glucose or other inducers such as 2-deoxy-d-glucose. Both PAO 57 and parental strain PAO transported glucose with an apparent K(m) of 7 μM. Free glucose was concentrated intracellularly by P. aeruginosa PAO 57 over 200-fold above the external level. These data constitute direct evidence that glucose is transported via active transport by P. aeruginosa. Various experimental data clearly indicated that P. aeruginosa PAO transported methyl α-d-glucose (α-MeGlc) via the glucose transport system. The apparent K(m) of α-MeGlc transport was 7 mM which indicated a 1,000-fold lower affinity of the glucose transport system for α-MeGlc than for glucose. While only unchanged α-MeGlc was detected intracellularly in P. aeruginosa, α-MeGlc was actually concentrated intracellularly less than 2-fold over the external level. Membrane vesicles of P. aeruginosa PAO retained transport activity for gluconate. This solute was concentrated intravesicularly several-fold over the external level. A component of the glucose transport system is believed to have been lost during vesicle preparation since glucose per se was not transported. Instead; glucose was converted to gluconate by membrane-associated glucose dehydrogenase and gluconate was then transported into the vesicles. Although this may constitute an alternate system for glucose transport, it is not a necessary prerequisite for glucose transport by intact cells since P. aeruginosa PAO 57, which lacks glucose dehydrogenase, was able to transport glucose at a rate equal to the parental strain.